Apparatus for connection to public telecommunications systems using the Digital Access Signalling System No. 2 (DASS 2) via a 2048 kbit/s CCITT Recommendation G.703 interface. Specification for automatic-repeat call attempt facilities Part 2, (29th November 1991) - British Standards Institution,
No abstract available